Microbes and the environment - Aspri, Maria; Tsaltas, Dimitrios (My University, 2020)
The production of traditional fermented meat or dairy products is a complex biological phenomenon affected by the action of indigenous microbes. These traditional manufacturing practices lead to a great variability in the quality and flavor of the products. Understanding the metabolic activities, diversity and behavior of microorganisms during food fermentations is a very interesting and challenging task. This will help the producers to reach high quality of their products in terms of safety, shelf life and organoleptic characteristics, as the most promising strains for starter cultures are those which are isolated from the indigenous microbiota of traditional products. The current chapter describes the microbial diversity of naturally fermented dairy and meat products in relation to processing environment and equipment as well as the impact on quality characteristics including authentication of origin and traditional making practices.
Keywords: Ecology; Fermentation; Food; House microbiota; High-thoughput sequencing; Lactic acid bacteria